Letramento literário na EJAEF : como abordar a ambiguidade sexual nos contos de Clarice Lispector - Santos, Fábio Silva (2016)
This TCF presents a proposal of literary literacy for classes of Educação de Jovens e Adultos of Elementary School from the debate on sexual identities and the ambiguity as this theme is approached by Clarice Lispector in the book A via crucis do corpo (1974). This proposal advocates the selection of literary texts for EJAEF with the purpose of promoting actions with the objective of guaranteeing the deserved importance to literary literacy in the process of formation of these readers. Our proposal was built through a field research, in a public school in the state of Sergipe, in the year 2016, which explored the reading of sexual ambiguity in the stories of Clarice Lispector. At the first moment, we mapped the horizon of expectation of these readers; Secondly, we included the debate on the flexibilities of sexual identities from the study of the behavior of the characters; During the third part, we proposed the reflection of how the sexual identities are built in the social context of these readers. Methodologically, we applied the theoretical concepts regarding the formation of the reader: "literary identity", of A. Rouxel, "literary literacy" articulated by H. Cosson and C. Gomes, "literary reading" in EJA, defended by M. Cruz. With regard to the debate on the construction of sexual identity, we took as reference the studies of M. Foucault, G. Louro and S. Hall, since they defend the temporariness of identity with various possibilities of social reconfigurations. As a result of this research, we present the report of the reading experience that aimed to broaden the reader's expectation horizon regarding the flexibility of sexual identities.This was possible because the reader, from his cultural horizon, assumes the role of collaborator in the process of producing meanings for the literary work. Therefore, this work seeks to broaden the debate on pleasing methods to plan our classes of literary readings in the classes of the EJAEF.